Carbon Monoxide Suppresses Neointima Formation in Transplant Arteriosclerosis by Inhibiting Vascular Progenitor Cell Differentiation. Issue 6 (15th April 2021) - Sakihama, Hideyasu; Lee, Ghee Rye; Chin, Beek Y.; Csizmadia, Eva; Gallo, David; Qi, Yilin; Gagliani, Nicola; Wang, Hongjun; Bach, Fritz H.; Otterbein, Leo E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Evidence indicates that bone marrow progenitor cells (BMPC) are a major contributor to neointima formation in transplant arteriosclerosis. HO-1 (heme oxygenase-1, Hmox1 ) and carbon monoxide (CO), a product of heme degradation by HO-1, ameliorate neointima formation by inhibiting proliferation of smooth muscle cells. We investigated the mechanism whereby HO-1 and CO modulate BMPC and mitigates neointima formation in transplant arteriosclerosis. Approach and Results: Using a murine model of aortic transplantation, bone marrow chimeric mice, and in vitro experiments, we report that CO does not inhibit mobilization of BMPC into the circulation or their homing to the vessel adventitia, but instead suppresses differentiation of BMPC into smooth muscle cells after they arrive in the adventitia. Specifically, the effect of CO on differentiation of BMPC into smooth muscle cell is mediated in part, by limiting PDGFR-β (platelet derived growth factor receptor-β) signaling. Hmox1 −/− BMPC exhibit a greater propensity to differentiate into smooth muscle cell in vitro, in part by regulating PDGFR-β + expression. Furthermore, wild-type mice transplanted with Hmox1 −/− bone marrow cells show augmented neointima formation after allografting versus control. CO exposure significantly ameliorated neointima formation, which remains more severe with Hmox1 −/− bone marrow cell versus air-treated mice receiving HO-1-expressing bone marrow cell, highlighting the importance of endogenous HO-1 in neointima formation. Conclusions: Host BMPC contribute to neointima formation in transplant arteriosclerosis and the protective effect afforded by HO-1/CO against neointima formation is mediated in part through the regulation of PDGFR-β expression. We propose that suppressing differentiation of BMPC is a major mechanism by which HO-1 and CO prevent neointima expansion after transplant.